Using projective exercises to identify patient perspectives of living with comorbid type 2 diabetes and asthma. (December 2021) - Litchman, Michelle L; Allen, Nancy A; McAdam-Marx, Carrie; Feehan, Michael
Objective: Patient self-management of a single chronic condition can be challenging, but few studies have examined the emotional impact of living with comorbid conditions and how that differs from a single chronic condition. This study examined patient perspectives of the emotional impact of living with asthma or asthma with comorbid type 2 diabetes (asthma+diabetes). Methods: Data were collected from 41 adults (asthma only n = 22, asthma+diabetes n = 19) using semi-structured interviews on two separate online bulletin boards. Respondents engaged in discussions that leveraged two projective exercises: describing their health condition(s) as an animal, and selecting one of eight images that best illustrated how they were living with and managing their health condition(s). Results: Respondents described physical and emotional challenges related to managing asthma or asthma+diabetes. Animal- and image- projective exercises were categorized by response and health condition. Thematic analysis across both projective exercises identified four themes: (1) frustrations with dual diagnosis, (2) juggling the dual diagnosis, (3) anticipating the future, and (4) unpredictability. Discussion: Projective exercises are one way to elicit feelings about living with chronic conditions. Healthcare providers can improve support for patients with more than one health condition by providing education on how to manage comorbid conditions.